Avaliação dos efeitos promovidos pela sibutramina, associada ou não à nicotina, nos tecidos reprodutivos de ratas albinas - Camargo, Isabel Cristina Cherici [UNESP]; Gonçalves, Juliana Grizante Segantin [UNESP] (My University, 2013)
Sibutramine is a drug recommended clinically for the treatment of obesity, but there are women that use the drug for maintenance of body weight. Many time this use occur associate to habit of tabagism, being the nicotine the main toxic compound in the cigarette. The goal of study was to evaluate the side effects promoted by sibutramine, associated or not to nicotine, in the reproductive tissue of adult female rats. Wistar animals (n =30), were distributed in the groups: a) Control A (0.3 mL of distilled water; oral); b) Sibutramine (15 mg/kg of body weight; oral); c) Control B (0.3 mL of saline solution; intraperitoneal); d) Nicotine (4.0 mg/kg of body weight; intraperitoneal); e) sibutramine + nicotine. The treatments were conducted during 30 consecutive days (single dose, daily). Sibutramine, associated or not to nicotine, affected the folliculogenesis and luteogenesis. There were significant alterations (p<0.05) in the thickness of uterine layers, considerate each treatment. In conclusion, the administration isolated of sibutramine or nicotine promoted deleterious effects in the reproductive tissues of female rats and these effects were potential in the group that received both drugs.

A sibutramina é recomendada clinicamente para o tratamento da obesidade, mas há mulheres que têm feito o uso do fármaco para manutenção do peso corpóreo. Muitas vezes este uso ocorre concomitantemente ao hábito do tabagismo, sendo a nicotina o principal composto tóxico no cigarro. O objetivo do estudo foi avaliar os efeitos colaterais promovidos pela sibutramina, associada ou não à nicotina, no tecido reprodutivo de ratas adultas. Fêmeas da linhagem Wistar (n=30) foram distribuídas nos grupos: a) Controle A (0,3 mL de água destilada; oral); b) Sibutramina (15 mg/kg de peso corpóreo; oral); c) Controle B (0,3 mL de solução fisiológica; intraperitoneal); d) Nicotina (4,0 mg/kg de peso corpóreo; intraperitoneal); e) Sibutramina + Nicotina. Os tratamentos foram realizados durante 30 dias consecutivos (única dose diária). O ciclo estral das ratas manteve-se regular durante o período experimental. A administração de sibutramina associada ou não à nicotina afetou a foliculogênese e luteogênese. Houve alterações significativas (p<0,05) na espessura das camadas teciduais uterina, em função de cada tratamento. Concluiu-se que a administração isolada de sibutramina ou nicotina promoveu efeitos deletérios nos tecidos reprodutivos de ratas e estes efeitos foram potencializados pela associação dos fármacos.
Assessment of the effects promoted by sibutramine, associated or not to nicotine, in reproductive tissues of albino female rats
Keywords: Sibutramine; Nicotine; Histomorphometry; Ovaries; Uterus; Rats; Sibutramina; Nicotina; Histomorfometria; Ovários; Útero; Ratas